Acquired life-threatening uterine arteriovenous malformation treated by endovascular embolization - Huynh, Chinh (Radiol Case Rep, 2020)
Uterine arteriovenous malformation (AVM) is a rare condition that may lead to a life-threatening state. The urgency of diagnosis and treatment for uterine AVM should be emphasized. This case report describes a 42-year-old woman with a vaginal hemorrhage. In the previous month, the patient also had a hemorrhage after induced abortion that required a bilateral artery suture hemostasis of the uterus. On ultrasound, there was a lesion suspected by acquired AVM. Magnetic Resonance Angiography and Digital Subtraction Angiography was indicated to confirm the diagnosis. The patient was successfully treated by uterine artery embolization. After 6 months, the re-examined result showed no lesion of AVM.